Boats testing in indoor tank - Kleshnev, V. (Rowing Biomechanics Newsletter, 2015)
Four singles of different brands were recently tested in an indoor tank (600m long, 16m wide, 7m depth, constant temperature +16oC) at Krylov State Research Centre in Saint-Petersburg, Russia. The boats were: · Empacher (X10 A115, 2013, 85-100kg); · Filippi (F14, 2011, 80-95kg); · Wintech (Medalist, 2014, 75-85kg); · Nowing (local boat builder, 2014, 75-85kg). The purposes of the test were to define the drag factors DF of each boat using two methods: rowing and towing, and then to find their correlation.